CREATIVE HUB DI BANJARBARU DENGAN KONSEP LAYERING - Nugroho, Muhammad Gilang; Heldiansyah, J.C (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
Vision Indonesia 2045 targets a significant economic improvement for the Indonesian nation. One of the points is to realize Indonesia as a World Class Center for Creative and Digital Economy. For this specific reason, a space is needed to develop human resources through Creative Space. Banjarbaru, is a city which is the capital of South Kalimantan, but there is a “dead” strategic zone in the center of the city. The Creative Space function can then be injected into the area as a form of area revitalization. The concept of layering is used through the superimposition method by dividing the area's functions into several layers, which are then stacked again to create a container for dynamic creative activity, as well as restoring the area's vitality value with new and diverse functions (mixed use).